A phase-I trial of pre‐operative, margin intensive, stereotactic body radiation therapy for pancreatic cancer: the 'SPARC' trial protocol. Issue 1 (December 2016) - Holyoake, Daniel; Ward, Elizabeth; Grose, Derek; McIntosh, David; Sebag-Montefiore, David; Radhakrishna, Ganesh; Patel, Neel; Silva, Michael; Mukherjee, Somnath; Strauss, Victoria; Odondi, Lang'o; Fokas, Emmanouil; et al.
Abstract Background Standard therapy for borderline-resectable pancreatic cancer in the UK is surgery with adjuvant chemotherapy, but rates of resection with clear margins are unsatisfactory and overall survival remains poor. Meta-analysis of single-arm studies shows the potential of neo-adjuvant chemo-radiotherapy but the relative radio-resistance of pancreatic cancer means the efficacy of conventional dose schedules is limited. Stereotactic radiotherapy achieves sufficient accuracy and precision to enable pre-operative margin-intensive dose escalation with the goal of increasing rates of clear resection margins and local disease control. Methods/Design SPARC is a "rolling-six" design single-arm study to establish the maximum tolerated dose for margin-intensive stereotactic radiotherapy before resection of pancreatic cancer at high risk of positive resection margins. Eligible patients will have histologically or cytologically proven pancreatic cancer defined as borderline-resectable per National Comprehensive Cancer Network criteria or operable tumour in contact with vessels increasing the risk of positive margin. Up to 24 patients will be recruited from up to 5 treating centres and a 'rolling-six' design is utilised to minimise delays and facilitate ongoing recruitment during dose-escalation. Radiotherapy will be delivered in 5 daily fractions and surgery, if appropriate, will take place 5–6 weeks after radiotherapy. The margin-intense radiotherapy concept includes a systematic method to define the target volume for a simultaneous integrated boost in the region of tumour-vessel infiltration, and up to 4 radiotherapy dose levels will be investigated. Maximum tolerated dose is defined as the highest dose at which no more than 1 of 6 patients or 0 of 3 patients experience a dose limiting toxicity. Secondary endpoints include resection rate, resection margin status, response rate, overall survival and progression free survival at 12 and 24 months. Translational work will involve exploratory analyses of the cytological and humoral immunological responses to stereotactic radiotherapy in pancreatic cancer. Radiotherapy quality assurance of target definition and radiotherapy planning is enforced with pre-trial test cases and on-trial review. Recruitment began in April 2015. Discussion This prospective multi-centre study aims to establish the maximum tolerated dose of pre-operative margin-intensified stereotactic radiotherapy in pancreatic cancer at high risk of positive resection margins with a view to subsequent definitive comparison with other neoadjuvant treatment options. Trial registration ISRCTN14138956 . Funded by CRUK